Error Pronouncing English Vowels - Napitupulu, Maya Farhan; Anwar , Hazril Fikri; Lubis , Yani (CV. Generasi Insan Rafflesia, 2023)
The National Exam (AN) replaces the national exam. This national assessment guideline is a form of quality assessment for each school, madrasah and equity program at the primary and secondary levels. Therefore, the National Assessment (AN) is not used to assess specific students, but to assess school quality. The results of the national evaluation of teachers and students will determine the quality of schools in the future. A national assessment policy will be established in 2021. Decree of the Minister of Education, Culture, Research and Technology Number 17 concerning National Assessment. The national assessment was created not only as a substitute for National Examination and national standard schools, but also as a paradigm for educational assessment. The National Assessment (Na) is used to monitor and evaluate the primary and secondary school systems. evaluate the elementary school system and Crystal. Based on the results, there are three types mistakes i English pronunciation, namely adding the vowels [e], [ɪ], [a], [ɜː], [ə]; vowel substitution [ə], [æ], [uː], [ɔː], [ɪ], [iː], [e], [ʌ], [ɑː], [ɒ], [ɜː], [aɪ], [aʊ], [ɪə], [eɪ], [əʊ], [ɔɪ], [eə], [aʊə]; and vocals omitted [ɪ], [ə], [a], [e].